Use of the Galleria mellonella Caterpillar as a Model Host To Study the Role of the Type III Secretion System in Pseudomonas aeruginosa Pathogenesis - Miyata, Sachiko (American Society for Microbiology, 2003)
Nonvertebrate model hosts represent valuable tools for the study of host-pathogen interactions because they facilitate the identification of bacterial virulence factors and allow the discovery of novel components involved in host innate immune responses. In this report, we determined that the greater wax moth caterpillar Galleria mellonella is a convenient nonmammalian model host for study of the role of the type III secretion system (TTSS) in Pseudomonas aeruginosa pathogenesis. Based on the observation that a mutation in the TTSS pscD gene of P. aeruginosa strain PA14 resulted in a highly attenuated virulence phenotype in G. mellonella, we examined the roles of the four known effector proteins of P. aeruginosa (ExoS, ExoT, ExoU, and ExoY) in wax moth killing. We determined that in P. aeruginosa strain PA14, only ExoT and ExoU play a significant role in G. mellonella killing. Strain PA14 lacks the coding sequence for the ExoS effector protein and does not seem to express ExoY. Moreover, using ΔexoU ΔexoY, ΔexoT ΔexoY, and ΔexoT ΔexoU double mutants, we determined that individual translocation of either ExoT or ExoU is sufficient to obtain nearly wild-type levels of G. mellonella killing. On the other hand, data obtained with a ΔexoT ΔexoU ΔexoY triple mutant and a ΔpscD mutant suggested that additional, as-yet-unidentified P. aeruginosa components of type III secretion are involved in virulence in G. mellonella. A high level of correlation between the results obtained in the G. mellonella model and the results of cytopathology assays performed with a mammalian tissue culture system validated the use of G. mellonella for the study of the P. aeruginosa TTSS.